2021
DOI: 10.3846/btp.2021.12832
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Capital Market Integration and Asymmetric Information: A Study in the Five Asean Countries From the Post-Global Financial Crisis

Abstract: This study aims at examining the integration impact of the five ASEAN Islamic capital markets on asymmetric information for ASEAN Economic Community (AEC) development. Utilizing samples of market and financial panel data from 2009 to 2015 among the five ASEAN Islamic capital markets, and applying two-country portfolios of the Islamic capital markets among the five ASEAN countries to measure the different levels of Islamic capital market integration, this study suggests that the different levels of the Islamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…The research revealed that market participants actively assess the lawfulness of their investments, ensuring that every entity they choose adheres to Islamic standards. Ethnomethodological analysis describes the process of careful assessment of a company's financial structure, revenue sources, and business practices, creating a clear dividing line between investments that are shariah-compliant and those that are not (Qizam, 2021). In addition, research findings state that socio-cultural factors are also a central point in making investment decisions.…”
Section: Factors Influencing Investment Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research revealed that market participants actively assess the lawfulness of their investments, ensuring that every entity they choose adheres to Islamic standards. Ethnomethodological analysis describes the process of careful assessment of a company's financial structure, revenue sources, and business practices, creating a clear dividing line between investments that are shariah-compliant and those that are not (Qizam, 2021). In addition, research findings state that socio-cultural factors are also a central point in making investment decisions.…”
Section: Factors Influencing Investment Decisionsmentioning
confidence: 99%
“…The Islamic capital market is also one of the investment instruments that is increasingly in demand by the people of Indonesia. This is evidenced by the increasing number of Islamic capital market investors in Indonesia (Qizam, 2021). Based on data from the Otoritas Jasa Keuangan (OJK), the number of Islamic capital market investors in Indonesia in 2022 reached 162,900 investors, an increase of 20.2% from the previous year (OJK, 2023).…”
Section: Introductionmentioning
confidence: 99%